The differential expression of osteoprotegerin (OPG) and receptor activator of nuclear factor κB ligand (RANKL) in human osteoarthritic subchondral bone osteoblasts is an indicator of the metabolic state of these disease cells - Tat, Steeve Kwan (Clin Exp Rheumatol, 2008)
OBJECTIVE: We previously reported that human OA subchondral bone osteoblasts could be discriminated into two subpopulations identified by their levels of endogenous production (low [L] or high [H]) of PGE(2). Here, we investigated the OPG and RANKL expression levels, the histologic analysis of the subchondral bone as well as the osteoclast differentiation effect of osteoblasts on normal and both OA subpopulations (L and H), and further examined on the L OA osteoblasts the modulation of bone remodelling factors on the OPG and RANKL levels, as well as on the resorption activity. METHODS: Gene expression was determined using real-time PCR, PGE(2) and OPG levels by specific ELISA, and membranous RANKL by flow cytometry. Histological observation of the subchondral bone was performed on human knee specimens. Osteoclast differentiation and formation was assayed by using the pre-osteoclastic cell line RAW 264.7. OPG and RANKL modulation on L OA osteoblasts was monitored following treatment with osteotropic factors, and the resorption activity was studied by the co-culture of differentiated PBMC/osteoblasts. RESULTS: Human OA subchondral bone osteoblasts expressed less OPG than normal. Compared to normal, RANKL gene expression levels were increased in L OA and decreased in H OA cells. The OPG/RANKL mRNA ratio was significantly diminished in L OA compared to normal or H OA (p<0.02, p<0.03), and markedly increased in H OA compared to normal. Inhibition of endogenous PGE(2) levels by indomethacin markedly decreased the ratio of OPG/RANKL on the H OA. In contrast to H OA osteoblasts, L OA cells induced a significantly higher level of osteoclast differentiation and formation (p<0.05). Histological analysis showed a reduced subchondral bone on the L OA and an increased bone mass on the H OA compared to normal. Treatment of L OA osteoblasts with osteotropic factors revealed that the OPG/RANKL mRNA expression ratio was significantly reduced by vitamin D(3) and significantly increased by TNF-α, PTH and PGE(2), while IL-1β demonstrated no effect. OPG protein levels showed similar profiles. No true effect was noted on membranous RANKL upon treatment with IL-1β, PGE(2) and PTH, but a significant increase was observed with vitamin D(3) and TNF-α. The resorption activity of the L OA cells was significantly inhibited by all treatments except IL-1β, with maximum effect observed with vitamin D(3) and PGE(2). CONCLUSION: OPG and RANKL levels, and consequently the OPG/RANKL ratio, differed according to human OA subchondral bone osteoblast classification; it is decreased in L and increased in H OA. These findings, in addition to those showing that L OA osteoblasts have a reduced subchondral bone mass and induce a higher level of osteoclast differentiation, strongly suggest that the metabolic state of the L OA osteoblasts favours bone resorption.